Tinjauan atas Segmenting, targeting, dan positioning pada PT Cimory Dairyland Puncak - Farhan, Maulana; Nurendah, Yulia (Jurnal Ilmiah Pariwisata Kesatuan, 2022)
Culinary is an activity related to cooking and is interpreted as processed products in the form of food or drinks. Culinary terms have spread widely in Indonesia so that currently culinary terms are often mentioned, heard, and read through print and audio-visual media. The purpose of this writing is to find out: 1). To find out the application of segmentation, targeting and product positioning at PT. Cimory Diary Land Puncak. 2). To find out the obstacles that occur 3). To find out how to deal with problems with PT. Cimory Diary Land Puncak products. The results of this scientific work show that: 1. Geographically, PT Cimory Dairyland Puncak divides its marketing area into several areas, especially on Jalan Puncak Bogor. Targeting is carried out to reach the target market based on the selected target size. The positioning carried out by PT Cimory Dairyland Puncak is positioning based on attributes, benefits, use or application, category and price with quality. 2. The obstacle for PT Cimory Dairyland Puncak is that it still uses outdated transaction tools and has poor SOPs. 3. In overcoming obstacles, time alignment is carried out. As well as carrying out maintenance related to the system being applied. Keywords: Application of Segmenting, Targeting and Positioning at PT Cimory Dairyland Puncak.